Stereoconvergent, photocatalytic cyclopropanation reactions of β-substituted styrenes with ethyl diazoacetate - Tim Langletz; Claire Empel; Sripati Jana; Rene M. Koenigs (Tetrahedron Chem, 2022)
Cyclopropanes constitute a pivotal molecular scaffold in medicinal and agrochemical research and find broad applications in marketed drugs and other bioactive compounds. Their synthesis commonly relies on metal-catalyzed carbene transfer reactions that necessitate the utilization of stereochemically defined olefin starting materials, which in turn requires a high stereochemical fidelity in the olefin synthesis step. Herein, we report on a photocatalytic strategy that allows the use of a mixture of the E- and Z-isomers of such olefins and gives access to a single isomer of the cyclopropane product in a stereoconvergent reaction. Experimental and theoretical data suggest the intermediacy of a triplet carbene intermediate that readily reacts with either isomer of the olefin. The intersystem crossing from triplet to singlet state proceeds in a diastereoselective fashion and can rationalize this stereoconvergent reaction. The application of this process was then examined with a diverse set of stereochemical mixtures of double- or triple-substituted olefins that readily undergo cyclopropanation disregarding of the stereochemical fidelity of the used olefin.